Risk factors for dog bites in Moiben Sub-county, Uasin Gishu county, Kenya - Tuwei, Philip Kipchoge; Kariuki, Stephen Mwaura (International Journal Of Community Medicine And Public Health, 2017)
Background: Rabies virus still causes human and animal deaths around the world. Human rabies is transmitted by an infected canine. If rabies-infected person is not treated within 48 hours, the virus could move to the central nervous system and cause irreversible cell damage that could be fatal. The aim of this study was to establish risk factors for dog bites in Moiben Sub-county, and whether there is a significant association between dog bite frequency and those risk factors. Methods: A total of 339 respondents were selected from a total of 1152 households using multistage sampling, simple random sampling and systematic sampling methods. The head of the household responded to interviewer-administered questionnaires. Data was analyzed using SPSS version 22 of 2013. Associations were tested using chi square test and any associations reported at critical p-value of 0.05 and 95% confidence interval. Results: This Study found more children <15 years bitten by dogs (351/643, 54.6%, X²=26.3, p<0.01) than any other age bracket. There were significantly more males bitten compared with female victims (334/643, 51.9%, X²=10.3, p=0.03). Strangers were bitten in larger numbers than family members (512/643, 79.6%, X²= 7.11, p=0.03). The unconfined dogs bit people than the partially confined dogs (487/643, 75.7%, X²=12.9, p=0.01). Most people were bitten during the wet season than in dry season (437/643, 67%, X²=18.8, p=0.01). Conclusions: The risk factors with significant association in dog bites in Moiben Sub-coounty were age and sex of the residents, dog confinement and seasons of the year. We recommend that the County government of Uasin Gishu controls the movement of dogs by enforcing the existing confinement policy and movement permits made mandatory for anyone intending to move a dog from one place to another. Free educational vaccination campaigns should be provided in order to attain 75% dog vaccination coverage.